2014
DOI: 10.26719/2014.20.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing parental consent for participation in clinical research involving their children in Egypt

Abstract: Factors affecting parents' decision to involve their children in clinical research have not been studied in all cultural backgrounds. We aimed to explore the attitudes and beliefs influencing parents' decision to involve their children in clinical research in Mansoura, Egypt. Of 523 families approached, 357 filled the questionnaire. Only 98 (27.5%) parents consented to involve their child in clinical research. The children of consenters were significantly older than refusers: 8.6 (SD 7.2) versus 2.6 (SD 1.2) y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…In our survey, vaccine trials appeared more appealing for participant enrollment than treatment-related trials (17.5% vs. 15%). The mentioned percentage is lower than the percentage reported from previous surveys conducted to assess people's agreement to participate in any clinical trial in the MENA region ( Al-Rawashdeh et al, 2019 , Altaf et al, 2019 , Gharaibeh et al, 2020 ; Lawati et al.,2018; Nasef et al.,2014 ). A public survey conducted in Saudi Arabia demonstrated that 26.9% of the participants were willing to participate in clinical trials ( Al-Rawashdeh et al,2019 ).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In our survey, vaccine trials appeared more appealing for participant enrollment than treatment-related trials (17.5% vs. 15%). The mentioned percentage is lower than the percentage reported from previous surveys conducted to assess people's agreement to participate in any clinical trial in the MENA region ( Al-Rawashdeh et al, 2019 , Altaf et al, 2019 , Gharaibeh et al, 2020 ; Lawati et al.,2018; Nasef et al.,2014 ). A public survey conducted in Saudi Arabia demonstrated that 26.9% of the participants were willing to participate in clinical trials ( Al-Rawashdeh et al,2019 ).…”
Section: Discussioncontrasting
confidence: 54%
“…To our knowledge, there is a scarcity of data pertaining to knowledge, attitude, and perception towards participation in clinical trials among the public from this region. A lot of published literature report data from the healthcare settings in the region ( Al-Dakhil et al, 2016 , Altaf et al, 2019 , Gharaibeh et al, 2020 ; Lawati et al,2018; Nasef et al.,2014 ). This study highlighted that only 15 to 17.5% of the surveyed people were willing to participate in COVID-19 clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 48% of the participants indicated that it is acceptable to test new drugs on paediatric participants. Objection to the use of new drugs or vaccines was one of the factors underlying the opposition to paediatric CTs 26. Although the study did not explore the reasons underpinning the objections to participating in CTs, we believe that the fear of adverse events, as well as safety concerns, may have been responsible 25 27…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, they stated that a complex informed consent form and misunderstanding of the term 'randomization' hindered parental approval of participation. In a study that was conducted in Egypt [11], found several factors that influence parental consent for participation in clinical research involving children in Egypt. The study found that factors favoring consent were: research of benefit to child, and enough explanation about the benefits that can be gained from the research.…”
Section: Discussionmentioning
confidence: 99%